Pengaruh Model Pembelajaran Problem Based Instruction (PBI) terhadap Kemampuan Penalaran Matematis Siswa - Nasution, Eline Yanti Putri; Gunawan, Rilla Gina; Yulia, Putri (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
This research was started by the lowerness of students’ mathematical reasoning ability at VII grade of SMPN 1 Kerinci. That’s obtained from the student’s semester examination result then according to the experience, observation and interview results with the junior high school mathematic teachers. The aim of this research is to analyze the effect of Problem Based Instruction (PBI) Model through student’s reasioning ability at VII grade of SMPN 1 Kerinci. This research is using quasy experiment method with Randomized Group Control Only Design. The population is all of seventh grade students in SMPN 1 Kerinci. This research is using Random Sampling Technique that students at VII-C grade as experimental group and VII-A grade as control group. The research instruments in this study is mathematical reasoning ability test to obtain students mathematical reasoning ability. The data is not have normal distribution so that we used Mann Whitney-U test with SPSS helped, obtained Sig (1-tailed). value = 0,000 α = 0,05 so that rejected H0. According to the analyzed of the data, the conclusion obtained that student’s mathematical reasoning ability who learn with using PBI Model is better than using conventional learning.